Prevalence of Tuberculosis in Coastal Communities of Port Harcourt City, Rivers State, Nigeria - Chikwendu Chinyere; Imarenezor Edobor Peter Kenneth (Darul Yasin Al Sys, 2026)
Tuberculosis (TB) remains a major public health challenge in Nigeria, with an estimated 586,000 incident cases in 2023, and coastal zones such as Port Harcourt present distinct epidemiological risks due to high population density, informal settlements, frequent flooding, and limited access to diagnostic and treatment services. Against the backdrop of scarce TB data specific to coastal communities and an almost complete absence of information on immunopathological mechanisms in this setting, this study examined TB prevalence and treatment compliance among residents of three coastal communities in Port Harcourt City, Rivers State—Eagle Island, Marine Base, and Borikiri Sea Side—and explored how risk factor exposure, preventive practices, attitudes, and knowledge relate to disease patterns. Using a descriptive cross-sectional design, 400 respondents completed a structured questionnaire capturing socio-demographic characteristics, TB-related knowledge, exposure to risk factors, preventive behaviors, attitudes, and treatment history, and the data were analyzed with descriptive statistics (frequencies, percentages, mean scores) and hypothesis testing. The findings show an overall TB prevalence of 11.5%, with community-specific prevalence of 12.0% in Eagle Island, 10.5% in Marine Base, and 12.5% in Borikiri Sea Side. Significant exposure to risk factors such as overcrowding, occupational hazards, and household tobacco smoke was positively correlated with TB prevalence (r = 0.462, p < 0.05). Moderate adoption of preventive measures (e.g., mouth covering and ensuring proper ventilation) was associated with better treatment compliance (r = 0.378, p < 0.05), although routine health check-ups were relatively uncommon. Positive attitudes toward TB—recognizing its seriousness and rejecting stigma—were linked to improved adherence (r = 0.421, p < 0.05), and higher TB knowledge similarly correlated with higher treatment compliance (r = 0.394, p < 0.05). The study concludes that TB control in these coastal communities requires an integrated strategy that simultaneously reduces exposure to structural and behavioral risk factors, strengthens preventive practices, promotes positive attitudes, and enhances TB-related knowledge. These context-specific insights provide an empirical basis for designing targeted public health interventions to improve treatment compliance and curb TB transmission in coastal Nigerian settings.